Health risk assessment Pb, as and cr in corn (Zea mays) of Behbahan and Dezful from Khuzestan Province, Iran - Zeinab Gholami; Maryam Mohammadi Rouzbahani; Khoshnaz Payandeh; Sima Sabzalipour (Scientific Reports)
Abstract Corn is one of the most important grains in the human food basket and is also widely cultivated in Iran. This research was conducted to evaluate the status of arsenic, lead, and chromium contamination in corn (Zea mays) samples grown in Dezful and Behbahan cities in Khuzestan province. In this research, five farms were randomly selected in each city, and from each field, five soil samples and five corn samples were prepared in the summer and autumn. A total of 50 soil samples and 50 corn samples were collected from the two study areas of Dezful and Behbahan cities in 2022. The average concentration of Pb, As, and Cr in corn samples was 1.84, 1.57, and 4.92 mg kg− 1, and in soil samples, 11.91, 4.02, and 76.86 mg kg− 1, respectively. The highest Transfer Factor (TF) for Pb, As, and Cr were 0.256, 0.762, and 0.128, respectively. The highest values of the CR index were obtained for lead, arsenic, and chromium, at 0.05, 8.40, and 9.27, respectively. According to the non-carcinogenic risk index (THQ) and carcinogenic risk index (CR), these metals can be dangerous for human health, but the THQ for Cr does not cause problems for adults and children.